2015
DOI: 10.1016/j.sbspro.2015.06.484
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of Urban Heat Island in Bangkok, Thailand

Abstract: The study focuses on the characteristics of urban heat island (UHI) in Bangkok, Thailand. Hourly air temperature data from four weather stations -one in rural site and three in urban sites for the last five year are used to study the characteristics and intensities of UHI in Bangkok area. The results indicate the presence of urban heat island in Bangkok and it is increasing in terms of intensity. The study reveals the maximum intensity of around 6-7°C is detected during dry season. The mean annual air temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 8 publications
2
22
0
Order By: Relevance
“…The observed increase in T min can be attributed to an increased intensity of the UHI during the hours after sunset and into the night. Many studies have previously shown that UHII is maximised during the night (Arifwidodo and Tanaka, ; Montávez et al , ; Ripley et al , ). The intensity is maximised during these hours, as heat absorbed by urban structures will be re‐radiated back into the atmosphere at a slower rate, due to smaller sky views, than natural structures.…”
Section: Discussionmentioning
confidence: 98%
“…The observed increase in T min can be attributed to an increased intensity of the UHI during the hours after sunset and into the night. Many studies have previously shown that UHII is maximised during the night (Arifwidodo and Tanaka, ; Montávez et al , ; Ripley et al , ). The intensity is maximised during these hours, as heat absorbed by urban structures will be re‐radiated back into the atmosphere at a slower rate, due to smaller sky views, than natural structures.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, the study done by Sheikh [31] shows that the average mean temperature in Bangkok was increased by 0.6 • C between 1985 and 2014. Arifwidodo and Tanaka [32] studied the effect of the Urban Heat Island (UHI) in Bangkok, showing that there is a mean maximum of 5 • C UHI intensity (UHII) between semi urban and urban areas, and a mean maximum UHII of 2 • C between dry and in rainy seasons. In addition, there is a maximum night time UHII of 7 • C during January in Bangkok [29,32].…”
Section: Study Areamentioning
confidence: 99%
“…Furthermore, shopping malls are part of a vicious environmental cycle. They contribute to Bangkok's urban heat island, which can be as high as 6–7 °C during the dry season (Arifwidodo, ), causing a city already oppressively hot to become even hotter and thereby driving more people to frequent malls.…”
Section: Bangkok's Incessantly Expanding Electricity Consumptionmentioning
confidence: 99%